INTERNALIZATION OF HUMANISTIC VALUES FOR EARLY AGES CHILDREN IN FACING PANDEMIC COVID-19 - Asfiati, Asfiati; Sutrisno, Sutrisno; Mahdi, Nur Imam; Aswin, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2020)
This research discusses the internalization of human values in children facing the COVID-19 pandemic in Padangsidimpuan. It was found that there were actions that were inappropriate for mothers, teachers and the community. Mothers understand the COVID-19 pandemic from a negative point of view. Mother forbids the children to see each other. The teacher advised the children not to leave the house. People advise children not to play outside of parental guidance. These are all inappropriate actions in understanding social distancing and staying at home as one of the government's appeals. However, it can follow play, study, and gather protocols. Therefore, it is necessary to conduct research on how the actions of mothers, teachers and society in children face the COVID-19 pandemic? How to internalize human values against the COVID-19 pandemic in Padangsidimpuan City? The results of the study found that mothers, teachers, and the community provided a more appropriate understanding of children and instilled the importance of being grateful to Allah SWT, feeling empathy for children whose parents were indicated to have COVID-19 and internalizing egalitarian, humanitarian attitudes, namely respect, care, share, strengthen hearts, and put forward identity so that life becomes useful.